Akanthou-Arkosykos, a ninth Millenium BC coastal settlement in Cyprus. (August 2015) - Sevketoglu, Muge; Hanson, Ian
Abstract : The site of Akanthou- Arkosykos, also known as Tatlısu- Çiftlikdüzü, (henceforth Akanthou) located on the north coast of Cyprus, been dated to Early Aceramic Neolithic or Cypro-PPNB/MPPNB 8200–7700 BC. It has been revealed as one of the most important early Aceramic Neolithic sites on Cyprus. Rescue excavations since 2000 were undertaken to assess the site and protect it from agricultural damage and threats from construction. The site is now a scheduled monument protected under the Antiquities law. Despite plough and other agricultural damage there is excellent preservation. The excavations have revealed six buildings of stone and mud brick architecture with round and rectilinear features and painted plastered walls and plaster floors. These are enclosed by a wide ditch to the south of the settlement. This feature contains hundreds of individual deposits reflecting the life of a sedentary community and evidence for human exploitation of marine life, domesticated plants and a variety of domestic and semi-domesticated animals. Obsidian finds numbering in excess of 4000 pieces represents the highest number of such finds from Cyprus so far. They have been demonstrated to be of central Anatolian origin and appear to have come to the site as finished products. Akanthou is 40 miles across the sea from the Anatolian mainland and is possibly a key-site that can answer questions regarding the origin of early settlers as well as early domestication and trade in Cyprus.